The Effect of Quality of Work Life, Job Satisfaction, and Job Commitment on Employee Performance Through Work Motivation in BPJS Employment Employees in the DKI Jakarta Region in 2023 - Rahman Irsyadi, Abdur (Dinasti International Journal of Digital Business Management, 2023)
Literature Review Article the Effect of Quality of Work Life, Job Satisfaction, Organisational Commitment, and Work Motivation on Employee Performance is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in further research, within the scope of Human Resource Management science. The method of writing this Literature Review article is by library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Quality of Work Life affects Employee Performance; 2) Job Satisfaction affects Employee Performance; and 3) Organisational Commitment affects Employee Performance; 4) Work Motivation affects Employee Performance; 5) Quality of Life, Job Satisfaction, Organisational Commitment and Work Motivation affect Employee Performance.